The role of IT management in driving digital transformation - Yarovyi, Hlib; Řepa, Václav, 1958-; Svatoš, Oleg; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2025)
This master’s thesis examines the strategic role of IT management in driving successful dig- ital transformation initiatives. Building on a conceptual framework combining strategic, process, and outcome layers, the study investigates how organizations balance formal gover- nance structures and agile delivery models. The research is based on multiple case studies conducted within Škoda Auto, Eaton Corporation, and Agrofert Group, representing diverse industrial sectors. Findings indicate that a strong strategic embedding of IT, supported by a combination of formal architecture modeling (MMABP) and agile practices, significantly contributes to achieving digital transformation outcomes such as operational efficiency, in- novation, and enhanced customer experience. The study also highlights the importance of effective risk mitigation and change management strategies during digital transformation processes. Implications for theory and practice are discussed, and propositions for future research are suggested.
Vedoucí práce: Václav Řepa
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: management of business informatics [obor dipl. práce]; diplomové práce; master's theses